A case of massive lower gastrointestinal bleeding from a rectal Dieulafoy lesion. Issue 3 (7th April 2015) - Lee, Yuan‐Kai; Bair, Ming‐Jong; Chen, Huan‐Lin; Lin, I‐Tsung; Wu, Chia‐Hsien
Summary: A Dieulafoy lesion is an uncommon and sometimes life‐threatening cause of gastrointestinal hemorrhage. Typically, it presents as a tiny mucosal defect with an exposed protruding artery with normal surrounding mucosa. An 84‐year‐old woman developed sudden massive hematochezia and had an unstable hemodynamic status. The source of bleeding was found to be an exposed vessel in the rectum without surrounding ulceration. The patient was treated successfully with an epinephrine injection given endoscopically, followed by hemostatic clipping.